SCIMPA FYP Management System - Ramli, Nur Anisah; Hibadullah, Cik Fazilah; Alwi, Asmidah (Multidisciplinary Applied Research and Innovation, 2021)
The Final Year Project (FYP) is a mandatory course to complete the study at the degree level. It is a final course for students and a platform where students can showcase and apply the knowledge and skills they obtained during classes and prepare for their internship in the industry. SCIMPA FYP is a web-based system for the management of FYP developed for the School of Creative Industry Management and Performing Arts (SCIMPA). The development of the system is to overcome the problems of the manual process of managing the FYP. The current practice is inefficient in terms of time and management of milestones to the students, inconvenience for supervisors and lecturers to safely manage the FYP documentation and submissions, the marking process, and lastly, the problem of archiving and retrieving past projects. Therefore, the objectives are to improve the efficiency of managing the current FYP and facilitate the archival and retrieval of past projects. The FYP system’s advantages can help users access online submission and retrieval, ensure data consistency within the community, improve efficiency in the management of FYP, and facilitate the archival and retrieval of past projects.